Metformin and Pitavastatin Alone and in Combination on Renal Function in Alloxan Induced Diabetic Rat - Jahan, Sarwat; Sakin, Saniad Ahmed; Moon, Kawsar Jahan; Islam, Tazin (Journal of Brahmanbaria Medical College, 2026)
Background: Type 2 diabetes has a strong association with dyslipidemia.Combination of antidiabetic and hypolipidemic drug are commonly practiced. Metformin, Pitavastatin and their combinations, widely used as therapeutic agents for diabetes and dyslipidemia. This study aimed to evaluate the renal safety by measuring serum creatinine levels in all groups of experimental rats. Materials and methods: 48 healthy male Wister strains of albino rats weighting to 180-220 gm aged between 10-12 wks were selected for the study. The experimental condition was all set in a very. Alloxan was prepared accordingly. The metformin and pitavastatin solution were prepared every 48hrs to maintain its activity. Data were analyzed using ANOVA in each variable. Results: In all six groups after two weeks treatment on day 15 The ranges of serum Creatinine in control group I were (0.3-0.9) mg/dl, diabetic control group IIA (0.7-1.2) mg/dl, metformin treated group IIB (0.3-1.1) mg/dl, pitavastatin treated group IIC (0.3-0.9) mg/dl, combination of metformin and pitavastatin treated group IID (0.3-0.8) mg/dl and group IIE (0.2-0.7) mg/dl. Here, significant difference in mean serum creatinine level in group IIA (0.97±0.18) against group I (normal control group-0.57±0.23), other groups were insignificant when compare to group I (Normal control group). The ranges of serum Creatinine Although levels were within normal limit in all groups. Conclusion: Metformin and pitavastatin combination might be an effective treatment in patients with both diabetes and dyslipidemia. As The ranges of serum Creatinine although levels were within normal limit in all groups. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 30-34